(untitled) (Herald of Journalism, 2022)
The article groups trends in the modern infosphere and analyzes their features. Moreover, the editorial policy of the National Press ("Egemen Qazaqstan", "Aikyn", "Qazaq adebieti") in the industrial and innovative era, information decisions and the importance of social phenomena, events and times from the perspective of the National Worldview are characterized. Today’s increase in cross-cultural integration and the impact of journalistic centers that strive to disseminate high-quality information from anywhere on the creation of a whole world information space obliges us to turn the National information science into new channels in a major flood of news. For this purpose, the research article focused on the peculiarities of mastering the new media sources of the newspapers: "Egemen Qazaqstan", "Aikyn", "Qazaq adebieti", which serve to meet the spiritual needs of a high-quality audience, analyzed the creative search and multicultural abilities of journalists who grew up during the liberation period in the management of spiritual, educational and recreational functions. This step in science will help to establish the proportion of global tolerance and national temperament and define domestic models in the new media age. By classifying creative and technical phenomena in the mass media, journalistic initiatives and audience awareness through comparative methodology, we could identify proposals and new directions. According to the results of the research, projects that expanded our media horizons, such as "Poetry corner", "Ornek", "Stadium", "Lessons on learning dombyra", "News in the new genre of storytelling "Shorts", "Photo chronicle", "Kobyz saryny", "Tanym" and "Let’s listen Kui", "Gifts for children", are in need of scientific evaluation. Of course, as scientific ideas, it is necessary to analyze the functional nature of these publications in conjunction with their actions in the transformation of new media. After all, the social activity of educational functions on the new media platform is always relevant. Keywords: communication, visualization, interface, navigation, artificial intelligence, press, national values.